Implementation of Virtual Reality-Based Neurorehabilitation in Neurological Nursing Practice - Kristiyawati, Sri Puguh; Riesmiyatiningdyah, Riesmiyatiningdyah (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examined the effectiveness of virtual reality (VR) in neurorehabilitation and explored nurses’ experiences in its implementation. Using a mixed-methods design with 60 neurological patients, the findings showed that the VR intervention group demonstrated significant improvements in motor function, cognitive function, and rehabilitation adherence compared to the control group. Qualitative results indicated that nurses found VR to enhance treatment strategies, although technical and facility limitations remained challenges. Overall, VR was proven effective in improving clinical outcomes and supporting neurological nursing practice through the integration of digital technology.